Defining bullying among students from criminal law perspective: Comparison between Malaysia and the Philippines - Rajamanickam R.; Ramli F.S.; Na'aim M.S.M.; Hassan M.S.; Hasnizam Hashim (Horizon Research Publishing, 2024)
Indexed by Scopus/ERA